2006
DOI: 10.37543/oceanides.v21i1-2.27
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the sea surface temperature and climatology of the Bay of La Paz, B.C.S., Mexico.

Abstract: Se analizaron 4175 imágenes diarias captadas con el sensor NOAA/AVHRR de julio de 1997 a diciembre de 2004, con el propósito de caracterizar la climatología y variación interanual de TSM en la Bahía de La Paz. A partir de la información se generaron 88 meses de anomalías de TSM y se realizó un análisis de componentes principa les (CP). Se obtuvieron tres componentes que explican en su conjunto el 50.32% de la varianza total de los datos originales de anomalías (32.68%, 11.95% y 5.69% respectivamente). El CP1 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
2
0
0
1
Order By: Relevance
“…A minimum value of 22.3 °C was recorded in April and a maximum of 29.2 °C in October. This variability is similar to that reported by other authors in Bahia de La Paz (Bernal et al, 2001;Martínez-López et al, 2001;Martínez-Flores, 2007) whom, in addition, observed slightly higher temperatures from August to October (30 to 31 °C), and lower from January to March (21 to 24 °C). According to this information, the population of L. dalli that inhabits Punta Diablo should be facing a thermal variability within a range of up to 10 °C.…”
Section: °Csupporting
confidence: 92%
See 1 more Smart Citation
“…A minimum value of 22.3 °C was recorded in April and a maximum of 29.2 °C in October. This variability is similar to that reported by other authors in Bahia de La Paz (Bernal et al, 2001;Martínez-López et al, 2001;Martínez-Flores, 2007) whom, in addition, observed slightly higher temperatures from August to October (30 to 31 °C), and lower from January to March (21 to 24 °C). According to this information, the population of L. dalli that inhabits Punta Diablo should be facing a thermal variability within a range of up to 10 °C.…”
Section: °Csupporting
confidence: 92%
“…Diel fluctuations in Bahia de La Paz sea surface temperature differ according to the time of the year; during cold months temperature changes approximately 1 °C, while during the warm period this variation is up to 2 °C (Martínez-Flores, 2007). This is similar to what was recorded in the present study, the diel variation in Punta Diablo during the sampling days was around 1 °C in both seasons.…”
Section: °Csupporting
confidence: 89%
“…La temperatura superficial del mar en la bahía de La Paz oscila entre 21 y 31°C a lo largo del año, alcanzando valores máximos entre julio y septiembre y mínimos entre enero y marzo (Martínez-Flores et al, 2006). El intervalo de clorofila-a en la zona presenta variaciones entre 0.26 y 2.41 mg/lt -1 , con un pico en invierno y concentraciones muy bajas en verano (Cervantes-Duarte et al, 2004); en consecuencia, durante la temporada fría la transparencia del agua es menor a 3 m, aunque se eleva hasta más de 8 m en meses cálidos (Cervantes-Duarte et al, 2001).…”
Section: Materiales Y Métodosunclassified